The coming wave : AI, power and our future / Mustafa Suleyman with Michael Bhaskar. - Suleyman, Mustafa; Bhaskar, Michael (Vintage, 2024)
We are about to cross a critical threshold in the history of our species. Everything is about to change. Soon we will live surrounded by AIs. They will carry out complex tasks - operating businesses, producing unlimited digital content, running core government services and maintaining infrastructure. This will be a world of DNA printers and quantum computers, engineered pathogens and autonomous weapons, robot assistants and abundant energy. It represents nothing less than a step change in human capability. We are not prepared. As cofounder of the pioneering AI company DeepMind, Mustafa Suleyman has been at the centre of this revolution, one poised to become the single greatest accelerant of progress in history. The coming decade, he argues, will be defined by this wave of powerful, fast-proliferating new technologies.